A critical study of the Turkish translations of Samuel Beckett's Krapp's Last Tape and its interpretations within the Turkish theatrical system - Dinçel, Burç İdem. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
This study explores the relationship between theatre criticism and theatre-translation criticism, with the purpose of challenging the tendency of Translation Studies to bypass theatre and that of Theatre Studies to attach little importance to the act of translation in performance. The thesis questions the dynamics of the two disciplines in the light of the research question that it seeks to answer: "when analysing a performance of a translated theatre work, what factors might a theatre-translation critic take into account?" In order to fulfil the needs of this question, moreover, the reasons behind the choice of studying the Turkish translations of Samuel Beckett‘s Krapp’s Last Tape and its interpretations within the Turkish theatrical system have been elucidated in the introductory part of the thesis. After providing a close look at the author‘s oeuvre and the position that Krapp’s Last Tape holds in the Beckett canon, the study examines the perception of Beckett‘s and that of Krapp’s Last Tape in Turkey in view of the systemic dynamics of the target culture. Furthermore, in order to move criticism from "page" to "stage" in theatre-translation criticism, the thesis proposes a model for the analysis of the performances of plays in translation that can simultaneously embrace the textual and scenic dimensions of theatre translations. As an application of the model, the Tiyatro-Z production of Krapp’s Last Tape has been analysed with the purpose of monitoring the acts of translation undertaken by the actor and director in the course of the performance. The findings of the thesis highlight the necessity of thinking theatre criticism and theatre translation criticism in relation to each other in terms of emancipating the act of translation and theatre from the bonds of the mutual neglect between the two disciplines.
Keywords: Translating and interpreting.